The nutritional quality and preference of wheat noodles incorporated with Caulerpa sp. seaweed - Agusman, Murdinah (2023)
Noodles are generally made from wheat flour, so their nutritional contents and characteristics depend on flour and other ingredients used. In the present work, fresh noodles were fortified with Caulerpa sp. filtrate in proportions of 0, 5, 10, 15, and 20%, and the quality and characteristics of fresh noodles obtained were determined. The assessments were conducted on the proximate compositions, dietary fibre, β-carotene, total phenolic content, textural properties, physical properties, and sensory qualities of noodles. The addition of Caulerpa sp. Filtrate increased the ash contents of noodles, and the ash contents of noodles were 1.45 ± 0.03 to 1.52 ± 0.04%. The β-carotene contents of noodles increased from 1.92 ± 0.19 to 3.68 ± 0.40 mg/kg with the addition of 15% Caulerpa sp. filtrate. Furthermore, total phenolic compounds were increased to a maximum of 85.2 ±1.82 mg GAE/100 g with the addition of Caulerpa sp. filtrate. The tensile strengths of noodles increased as Caulerpa sp. filtrate increased, while the elongations of noodles slightly decreased with the addition of Caulerpa sp. filtrate. The brightness of noodles decreased, and the greenness increased with the addition of Caulerpa sp. filtrate. Noodles with 15 and 20% Caulerpa sp. filtrate had significantly higher cooking yields than noodles without Caulerpa sp. filtrate. Consumer acceptance of noodles was not affected by Caulerpa sp. filtrate. Caulerpa sp. noodles could be a nutritional benefit for daily diets since they contain more β-carotene, minerals, and phenolic compounds